Preterm Infant Breastfeeding Behavior Scale: A study for Assessing the Validity and Feasibility - Mahboubeh Jamehdar; Roghaiyeh Nourizadeh; Aboulhassan Divband; Mohammadbager Hosseini; Leila Valizadeh; Sevil Hakimi (Mashhad University of Medical Sciences, 2022)
Background: Breastfeeding is known as a normative means of infant feeding, and human milk is considered the optimal nutrition source for infants. Although there are several tools for assessing infants' feeding behavior, currently, only the Preterm Infant Breastfeeding Behavior Scale (PIBBS) is specifically developed to measure the feeding behavior of preterm infants. The present study aimed to evaluate the validity and feasibility of PIBBS. Methods: The Preterm Infant Breastfeeding Behavior Scale was translated using forward/backward methods. Cohen's kappa coefficient was used to evaluate the inter-rater reliability of the questionnaire. To this end, the feeding behaviors of 70 neonates born at 32-35 weeks of gestation were assessed on two consecutive days, once by the researcher and again in the evening shift of the same day by one of the nurses, and then, PIBBS questionnaire was completed. The internal consistency of the instrument was measured by calculating Cronbach's alpha coefficient. Results: The total Cohen's kappa of the instrument was estimated to be 0.72 on the first day of observation and 0.79 on the second day, which was considered substantial. The Cronbach's alpha coefficient of the instrument was 0.791, which was acceptable. Conclusion: The PIBBS was a valid and reliable instrument for the evaluation of preterm newborns' feeding behavior.